Oxford Handbooks Online 2012
DOI: 10.1093/oxfordhb/9780198568926.013.0036
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent TMS and functional magnetic resonance imaging: methods and current advances

Abstract: Transcranial magnetic stimulation is used for a wide range of applications in cognitive, clinical, and neuroscience. However, the precise physiological mechanisms by which TMS influences brain function are only partially understood. Combining TMS with functional magnetic resonance imaging (fMRI) provides a more complete picture of the neural underpinnings of TMS effects. This article gives an overview of methodology and technical aspects concerned with combining TMS with fMRI. Furthermore, it explains the chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…For these experiments, methods were developed to avoid artifacts , signal loss during the acquisition , and to find the most suitable rTMS protocols or cortical targets . Reviews of the applications and methodology in concurrent TMS/fMRI can be found in the literature .…”
Section: Introductionmentioning
confidence: 99%
“…For these experiments, methods were developed to avoid artifacts , signal loss during the acquisition , and to find the most suitable rTMS protocols or cortical targets . Reviews of the applications and methodology in concurrent TMS/fMRI can be found in the literature .…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on fMRI and EEG, the examples discussed in this review establish principles and ideas that similarly apply to other imaging modalities. Finally, for safety considerations, technical and methodological details, and requirements for combining TMS with neuroimaging, the reader may refer to previous publications …”
Section: Introductionmentioning
confidence: 99%
“…Finally, for safety considerations, 14,20,21 technical and methodological details, and requirements for combining TMS with neuroimaging, the reader may refer to previous publications. 14,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] The below discussion is divided into three parts, the past, present, and potential future contributions to the field. First, early work, particularly in the motor system, is reviewed that provided evidence for the anatomically distributed effects of TMS.…”
Section: Introductionmentioning
confidence: 99%
“…The right dlPFC was the target for stimulation so we analysed it separately from the rest of the MD system ( Figure 5, right panels). It is typical not to see effects at the stimulation site with our setup (Bestmann, Ruff, Driver, & Blankenburg, 2008), one reason for this being that the TMS coil may shield this part of the cortex from MR excitation and readout. Although the trend appeared to be in the same direction as the rest of the MD system, our ANOVA 29 (factors TMS, Feature, and Relevancy) detected no significant main effects or interactions (all ps > 0.2, all BF10 < 0.46).…”
Section: Right Dlpfc (Stimulated Site)mentioning
confidence: 99%